Advances in Fmoc solid‐phase peptide synthesis. (20th January 2016) - Behrendt, Raymond; White, Peter; Offer, John
Abstract : Today, Fmoc SPPS is the method of choice for peptide synthesis. Very‐high‐quality Fmoc building blocks are available at low cost because of the economies of scale arising from current multiton production of therapeutic peptides by Fmoc SPPS. Many modified derivatives are commercially available as Fmoc building blocks, making synthetic access to a broad range of peptide derivatives straightforward. The number of synthetic peptides entering clinical trials has grown continuously over the last decade, and recent advances in the Fmoc SPPS technology are a response to the growing demand from medicinal chemistry and pharmacology. Improvements are being continually reported for peptide quality, synthesis time and novel synthetic targets. Topical peptide research has contributed to a continuous improvement and expansion of Fmoc SPPS applications. Copyright © 2015 European Peptide Society and John Wiley & Sons, Ltd. Abstract : Almost 40 years after its introduction, Fmoc/ tert ‐butyl chemistry is still an area of dynamic research. This review examines the latest advances in the method and highlights scope for further developments.